Diversity and Abundance of Ants (Hymenoptera: Formicidae) from Thiruthangal, Sivakasi (Taluk), Tamil Nadu - B Manikandan; P Anusuyadevi; SP Sevarkodiyone (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2018)
The present study deals with the diversity of ants in three different sites of Thiruthangal, Sivakasi Taluk, Virudhunagar (Dist.), India. During the present study four subfamilies are noted. Myrmicinae is a dominant subfamily in three study sites. Dolichoderinae has a low relative abundance during the study period.